Factors affecting survival after liver retransplantation: a systematic review and meta-analysis - Brombosz, Elizabeth W.; Moore, Linda W.; Mobley, Constance M.; Kodali, Sudha; Saharia, Ashish; Hobeika, Mark J.; Connor, Ashton A.; Victor, David W.; Cheah, Yee Lee; Simon, Caroline J.; Gaber, Ahmed Osama; Ghobrial, Rafik Mark (Frontiers in Transplantation, 2023)
Background Liver retransplantation (reLT) has historically had inferior survival relative to primary liver transplant (LT). To improve outcomes after reLT, researchers have identified factors predicting overall (OS) and/or graft survival (GS) after reLT. This systematic review and random effects meta-analysis sought to summarize this literature to elucidate the strongest independent predictors of post-reLT. Methods A systematic review was conducted to identify manuscripts reporting factors affecting survival in multivariable Cox proportional hazards analyses. Papers with overlapping cohorts were excluded. Results All 25 included studies were retrospective, and 15 (60%) were single-center studies. Patients on pre-transplant ventilation (HR, 3.11; 95% CI, 1.56–6.20; p = 0.001) and with high serum creatinine (HR, 1.46; 95% CI, 1.15–1.87; p = 0.002) had the highest mortality risk after reLT. Recipient age, Model for End-Stage Liver Disease score, donor age, and cold ischemia time >12 h also conferred a significant risk of post-reLT death (all p < 0.05). Factors affecting GS included donor age and retransplant interval (the time between LT and reLT; both p < 0.05). OS is significantly higher when the retransplant interval is ≤7 days relative to 8–30 days (p = 0.04). Conclusions The meta-analysis was complicated by papers utilizing non-standardized cut-off values to group variables, which made between-study comparisons difficult. However, it did identify 7 variables that significantly impact survival after reLT, which could stimulate future research into improving post-reLT outcomes.